Peningkatan Kemampuan Berbicara Siswa Autisme Melalui Penggunaan Game Autispark di SLB N 1 Binjai - Rangkuti, Fatimatun Zahara; Marlina, Marlina (Universitas Negeri Padang, 2024)
This research discusses the autism park game to improve students' speaking skills in saying numbers 1 to 10 for autistic children. This research aims to prove that the Autismark game is effective in improving the speaking skills of class V autism students at SLB N 1 Binjai. This research uses classroom action research, namely research intended to improve the quality of teaching practices in the classroom. From the results of the research, using game media can improve the measuring ability of grade IV mildly mentally retarded students at SLB N Padangsidimpuan. This classroom action research was carried out by implementing action activities to improve speaking ability to say numbers 1 to 10 using the autismpark game media. Judging from the results of the implementation, the children's work has increased from the provision of actions in cycle I to cycle II. From the results obtained, the child's initial ability was A 50%, then action was given in cycle I to increase it to A 70%, then continued in cycle II, the child's ability further increased to A 80%. In implementing measurement activities, it can be adjusted to the child's ability to receive learning.